2012
DOI: 10.1111/j.1365-2699.2011.02645.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of environmental heterogeneity and spatial distance in generating phylogeographic structure in edaphic specialist and generalist tree species of Protium (Burseraceae) across the Amazon Basin

Abstract: Aim  Edaphic heterogeneity may be an important driver of population differentiation in the Amazon but remains to be investigated in trees. We compared the phylogeographic structure across the geographic distribution of two Protium (Burseraceae) species with different degrees of edaphic specialization: Protium alvarezianum, an edaphic specialist of white‐sand habitat islands; and Protium subserratum, an edaphic generalist found in white sand as well as in more widespread soil types. We predicted that in the eda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 66 publications
(123 reference statements)
3
59
0
Order By: Relevance
“…(Left) A Bayesian phylogeny based on three nuclear genes of Protium subserratum populations from Fine et al (2013) showing white-sand ecotypes from Peru (white circles, triangles, and squares), terra firme ecotypes from Peru (gray circles, triangles, and squares), and terra firme ecotypes from Manaus Brazil (indicated with ''M''). First, we used generalized linear models and a negative binomial error structure to compare the number of insects and morphospecies observed per plant and the number of host plants on which morphospecies were collected with crossed predictors of habitat type and FIG.…”
Section: Insect Herbivore Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…(Left) A Bayesian phylogeny based on three nuclear genes of Protium subserratum populations from Fine et al (2013) showing white-sand ecotypes from Peru (white circles, triangles, and squares), terra firme ecotypes from Peru (gray circles, triangles, and squares), and terra firme ecotypes from Manaus Brazil (indicated with ''M''). First, we used generalized linear models and a negative binomial error structure to compare the number of insects and morphospecies observed per plant and the number of host plants on which morphospecies were collected with crossed predictors of habitat type and FIG.…”
Section: Insect Herbivore Samplingmentioning
confidence: 99%
“…Of these species, Protium subserratum Engl. Although there are consistent morphological differences that characterize the terra firme and white-sand ecotypes, there is also evidence of limited gene flow (or incomplete lineage sorting) between the two ecotypes (Fine et al 2013). comprises morphologically divergent ecotypes that correspond to white-sand and terra firme habitats, often occurring within meters of one another in a parapatric distribution Fine 2011, Fine et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3, 4). Interestingly, a phylogeographic study of Peruvian WS, BS, and CS ecotypes showed no variation in haplotypes between BS and CS individuals (Fine et al 2013b). Microsatellite studies are thought to reflect much more recent signals of population-level divergence than sequence data (Misiewicz and Fine 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They are morphologically distinct and often occur within meters of each other in a parapatric distribution (Fine et al 2013a;Misiewicz and Fine 2014). Phylogeographic analyses of the haplotypes of these three morphotypes as well as detailed population genetic study have revealed that they represent three evolutionary lineages although there is limited gene flow among them (Fine et al 2013b;Misiewicz and Fine 2014). Thus, these ecotypes either represent recently derived species or lineages undergoing incipient speciation.…”
Section: Introductionmentioning
confidence: 99%
“…(Burseraceae) is a widespread species found in northern Amazonia, extending into Guyana, French Guyana, the Brazilian Amazon, Ecuador, Peru, Colombia and Venezuela. This dioecious tree species occurs across a range of soil types including clay, sandy clay and white sand [22] and its red fruits are thought to be dispersed by birds and monkeys [23]. We studied a population of P. subserratum along an edaphic and topographic gradient within the Reserva Florestal Adolpho Ducke (hereafter referred as Ducke), where this species is found across a soil gradient that transitions from sandy soil in low elevation areas (39 m a.s.l.)…”
Section: Methodsmentioning
confidence: 99%